2021
DOI: 10.1186/s12879-021-06180-x
|View full text |Cite
|
Sign up to set email alerts
|

Long -term persistence of antibodies against varicella in fully immunized healthcare workers: an Italian retrospective cohort study

Abstract: Background Chickenpox is a highly contagious disease caused by the varicella zoster virus (VZV), and in infants, adolescents, adults, pregnant women, and the immunocompromised it can be serious. The best way to prevent chickenpox is immunization with the varicella vaccine. Protective levels of antibodies induced by the varicella vaccine decline over time, but there is currently no formal recommendation for testing anti-varicella zoster virus (VZV) IgG levels in immunized healthcare workers (HCW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…8-9). The authors suggested a third dose of vaccine to restore protection to avoid the risk of future varicella outbreaks [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…8-9). The authors suggested a third dose of vaccine to restore protection to avoid the risk of future varicella outbreaks [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…The incidence of HZ in vaccinated adults remains unknown and will need to be studied as the first vaccinated cohort ages. Reactivation of v-VZV has been documented and can lead to HZ [ 33 , 53 , 54 ]. With vaccine efficacy declining annually and resultant waning of specific anti-VZV immunity, there will continue to be a segment of the population susceptible to breakthrough varicella, who may experience varicella at older ages, when illness is more severe, and who may experience the higher rates of reactivation of wt-VZV as HZ.…”
Section: Reviewmentioning
confidence: 99%
“…Many persons who are vulnerable to varicella may become infected later in life. By 2021, about 40% of school-age children had not been vaccinated with VarV, we know that the level of antibody protection induced by VarV decline over time, and the results of studies by Francesco Paolo Bianchi 29 and Pasquale Stefanizzi 30 , 31 found that booster dose was effective and safe in achieving seroconversion. In addition, the safety profile of measles, mumps, rubella and varicella (MMRV) vaccine have been confirmed by post-market adverse event surveillance data, which can eliminate the concerns of some children’s parents about the long-term immunogenicity and safety of VarV and improve the compliance of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of health personnel to Vzv appears to be country-dependent, ranging from 5% to 50% [ 32 , 35 ]. Two Italian studies [ 36 , 37 ] evaluated circulating anti-Vzv IgG in fully vaccinated young HCWs and reported a prevalence of serosusceptibility ranging from 21 to 34%. This strong dissimilarity could be associated with the dissimilarity in the average age and immunization status of the populations being analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…MMR vaccination seems to be a protective factor for seroprotection, probably because of the goal of rubella (and measles) elimination and the associated vaccination campaign, whereas the Vzv-vaccine seems to be correlated with an improved risk of susceptibility at serologic evaluation. Indeed, as reported by many studies in the literature [ 36 , 37 ], the time from Vzv vaccination to evaluation of antibody level is a major factor of the decay in serum of circulating antibodies and thus protection against the wild virus; in particular, it appears that for the MMR vaccine, the duration of circulating antibodies is more than twice that of Vzv vaccine [ 36 ].…”
Section: Discussionmentioning
confidence: 99%